LEGAL MEASURES REGARDING ELDERLY CARE ESTABLISHMENTS: A CASE STUDY OF STANDAEDIZATION FOR CAREGIVERS FOR ELDERLY - Phawapanyakun, Arthitaya (Rangsit Journal of Law and Society, 2024)
Elderly means people aged 60 years and over. In this age there will be many changes. Physically, mentally, emotionally, and socially, old age is a transition period in life which changes from middle age to old age. These changes are in decline. There are limitations in the body's functioning in one or more areas. Therefore, elderly people need proper care. But in today's society Some families are unable to care for the elderly. Because I have to go out and do business to earn a living. Therefore, the business of establishments providing care for the elderly was born. To meet the needs of today's society According to the study, it was found that the standardization of caregivers for the elderly in Thailand, according to the ministerial regulations which determine the standards for places, safety, and services in health establishments in the category of elderly care or dependents, B.E. 2563, does not cover the standards in the aged care profession owing to the fact that the standardization of the ministerial regulations is merely a preliminary standardization, and does not define the specific qualifications, inspections, penalties, and details relevant to caregivers for the elderly. Additionally, at present, most of the persons who act or work as caregivers for the elderly in Thailand are workers from neighboring countries, which is not specified in the qualifications of this labor type in the ministerial regulations in any way. Therefore, it is deemed appropriate to propose an amendment to the standard of caregivers for the elderly in terms of qualifications, competency assessment, inspection, and penalties for both Thai and foreign caregivers for the elderly. Moreover, there should be an agency or committee to control and supervise those who work as caregivers for the elderly.